Variations in biomass and coumarin content of Justicia pectoralis Jacq.: Influence of season, harvest frequency and shade level. (February 2022) - de Lima, Pauline Zonta; de Freitas Morel, Lucas Junqueira; Pinto, Gustavo Henrique Teixeira; Contini, Silvia Helena Taleb; Crevelin, Eduardo José; do Nascimento Júnior, José Elvino; de Castro França, Suzelei; Bertoni, Bianca Waléria; Soares Pereira, Ana Maria
Abstract: Coumarin and umbelliferone are the active principles of Justicia pectoralis, a native Brazilian medicinal plant that is threatened by overexploitation and habitat fragmentation. Considering that its cultivation under appropriate conditions would be more sustainable than wild collection, here we examined how season, developmental stage, harvesting frequency, and light intensity affect the agronomical characteristics and chemical profile of a high-yield J. pectoralis genotype . Plants were propagated from cuttings, transplanted to experimental plots, and grown on under full sunlight or 50% and 80% shading. Plants were harvested after 3, 6, 9, and 12 months of growth, or pruned at these time points in a manner that allowed their regrowth over further 3 months. Chemical analysis of extracts from the aerial parts was performed by UPLC and HPLC. Cultivation under full sunlight or 50% shade promoted plant growth and production of coumarins the most effectively. Accumulation of coumarin and fresh and dry biomass were maximal in 12-month-old plants harvested in the summer, when the temperature was high, rainfall abundant, and flowering had terminated. The highest levels of umbelliferone were detected in 6-month-old flowering plants harvested in the winter, when the temperature was low and rainfall limited. The capacity of plants to accumulate biomass and coumarins did not decline with successive pruning and regrowth; hence, the genotype could be exploited in a continuous and systematic manner without frequent replanting. The results presented herein contribute to the large-scale cultivation of J. pectoralis and preparation of phytomedicines of quality. Highlights: Full sunlight or 50% shade favor Justicia pectoralis growth and coumarin production. Coumarin accumulation peaks in 12-month-old plants harvested in the summer. Umbelliferone accumulation peaks in 6-month-old plants harvested in the winter. Fresh and dry biomass are maximal in 12-month-old plants harvested in the summer. Successive pruning and regrowth do not affect accumulation of biomass and coumarins.